2022
DOI: 10.1038/s41598-022-21665-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Venetin-1 nanoparticle from earthworm coelomic fluid as a promising agent for the treatment of non-small cell lung cancer

Abstract: The present research shows the antitumor activity of a protein-polysaccharide complex Venetin-1 obtained from the coelomic fluid of Dendrobaena veneta earthworms against A549 cancer cells. The investigations are a continuation of experiments on the antitumor activity of coelomic fluid obtained from this species. The Venetin-1 nanoparticle was obtained after thermal treatment of the coelomic fluid, separation from coelomocytes, filtration, and lyophilization. The preparation showed a selective effect on cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The analysis of the Venetin-1 complex by Cryo-TEM confirmed the nanoparticle size determined by the DLS analysis 25 . The nanoparticles were visible under the microscope as spherical forms, which sometimes coalesced to form double forms indicated by red arrows in Fig.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The analysis of the Venetin-1 complex by Cryo-TEM confirmed the nanoparticle size determined by the DLS analysis 25 . The nanoparticles were visible under the microscope as spherical forms, which sometimes coalesced to form double forms indicated by red arrows in Fig.…”
Section: Resultssupporting
confidence: 69%
“…Following the analysis of Venetin-1 size (58.23 ± 3.93 nm) 25 conducted with the use of Prometheus Panta, a temperature melting experiment with a temperature gradient from 25 to 95 °C and a heating ramp of 1 °C/min was performed. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was stated that the cytotoxic effect of CF of E. eugeniae was superior, followed by CF of P. excavatus. Rybicka et al (2022) investigated the antitumour effects of Venetin-1, a protein-polysaccharide complex obtained from CF of D. veneta, against to lung cancer cell line A549 cells and found that the cells died by apoptosis. In another study with CF of D. veneta, the active protein-carbohydrate fraction isolated from CF disrupted the cell cycle in human colon adenocarcinoma (HT-29 and LS180) cell lines, inhibited 20S proteasome activity, and procaspase-3 (Czerwonka et al 2020).…”
Section: Permana Et Al (2019) Tested Cf Of Lumbricus Rubellusmentioning
confidence: 99%